Combined effects of surface plasmon coupling and Förster resonance energy transfer on the light color conversion behaviors of colloidal quantum dots on an InGaN/GaN quantum-well nanodisk structure. (8th January 2021) - Chen, Yen-Po; Ni, Chia-Chun; Wu, Ruei-Nan; Kuo, Sheng-Yang; Su, Yu-Cheng; Huang, Yang-Yi; Chen, Jia-Wei; Hsu, Yi-Chiao; Wu, Shung-Hsiang; Chen, Chien-Yu; Wu, Ping-Hsiu; Kiang, Yean-Woei; et al.
Abstract: By forming nanodisk (ND) structures on a blue-emitting InGaN/GaN quantum-well (QW) template, the QWs become close to the red-emitting quantum dots (QDs) and Ag nanoparticles (NPs) attached onto the sidewalls of the NDs such that Förster resonance energy transfer (FRET) and surface plasmon (SP) coupling can occur to enhance the efficiency of blue-to-red color conversion. With a larger ND height, more QWs are exposed to open air on the sidewall for more QD/Ag NP attachment through QD self-assembly and Ag NP drop casting such that the FRET and SP coupling effects, and hence the color conversion efficiency can be enhanced. A stronger FRET process leads to a longer QD photoluminescence (PL) decay time and a shorter QW PL decay time. It is shown that SP coupling can enhance the FRET efficiency.